2020
DOI: 10.1063/1.5142692
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of polymer-bonded anisotropic magnets in an external magnetic field and by a modified production process

Abstract: The possibility of producing polymer-bonded magnets with the aid of additive processes, such as 3D printing, opens up a multitude of new areas of application. Almost any structures and prototypes can be produced costeffectively in small quantities. Extending the 3D printing process allows the manufacturing of anisotropic magnetic structures by aligning the magnetic easy axis of ferromagnetic particles inside a paste-like compound material along an external magnetic field. This is achieved by two different appr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 21 publications
(16 reference statements)
0
17
0
Order By: Relevance
“…1) indicated that a shorter soft-curing of 30 minutes is better suited to structures of width < 100 µm, meaning the powder appears homogeneously distributed in the binder, while the longer time of 60 minutes is better suited to larger structures. The results presented hereafter concern arrays of micro-pillars made using a Si mould prepared with a mask of square features with in-plane dimensions 300x300 μm 2 . The Si was etched 300 μm in depth, and the width of the etched holes tapered down from 300 µm at the surface of the mould to roughly 200 µm at the base of the etch.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) indicated that a shorter soft-curing of 30 minutes is better suited to structures of width < 100 µm, meaning the powder appears homogeneously distributed in the binder, while the longer time of 60 minutes is better suited to larger structures. The results presented hereafter concern arrays of micro-pillars made using a Si mould prepared with a mask of square features with in-plane dimensions 300x300 μm 2 . The Si was etched 300 μm in depth, and the width of the etched holes tapered down from 300 µm at the surface of the mould to roughly 200 µm at the base of the etch.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, bonded magnets are widely used for the following reasons: firstly, they are cheaper than sintered versions in both material and fabrication cost, secondly, they can be easily manufactured in complex geometries, and finally, the mechanical properties can be tuned according to the choice of matrix. Traditional fabrication routes for polymer bonded magnets include calendering, injection moulding, extrusion, and compression bonding [1] while more recently 3D printing of polymer bonded magnets has been explored, in some cases down to the mm size range [2]- [7]. Down-scaling the size of magnets opens new opportunities for their use in micro-devices with applications in fields as diverse as telecommunications, energy management and bio-medicine.…”
Section: Introductionmentioning
confidence: 99%
“…At that position, an undesired force acting on the magnetic particle could lead to the unfavorable magnetization of the sample. [ 29 ]…”
Section: Preparation Of Materials and Printing Setupmentioning
confidence: 99%
“…The dimensions of magnets are therefore limited by the compaction mold. Additive manufacturing currently opens up opportunities for unconventional designs of rare-earth magnets [1][2][3][4][5], hard ferrites [5,6], and iron oxides [7,8], as well as recycled magnets [9]. Novel magnets of varying shapes and sizes can be printed out.…”
Section: Introductionmentioning
confidence: 99%